2006
DOI: 10.1161/01.atv.0000227510.36653.ed
|View full text |Cite
|
Sign up to set email alerts
|

Familial Elevated Factor VIII in Children With Symptomatic Venous Thrombosis and Post-Thrombotic Syndrome

Abstract: Objective-To evaluate the role of factor (F) VIII in children with non-cancer related venous thrombosis (DVT), post-thrombotic syndrome (PTS) or recurrent DVT. Methods and Results-FVIII levels were measured in White patients and age-and gender-matched healthy controls.Heritability of factor VIII was estimated in 99 pedigrees by the variance component method implemented in SOLAR. Key Words: factor VIII and children Ⅲ body mass index Ⅲ venous thrombosis Ⅲ post-thrombotic syndrome Ⅲ recurrent thrombosis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
2

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 42 publications
3
81
2
Order By: Relevance
“…164 Among a total of 977 patients with UEDVT/lower-extremity DVT, the weighted mean frequency of PTS was 26% (95% CI, [23][24][25][26][27][28]. When restricted to the 9 prospective analyses, [165][166][167][168][169][170][171][172][173] this frequency was 17% (95% CI, [14][15][16][17][18][19][20]. Only 1 prospective study has subsequently been published, in which the cumulative incidence of PTS was 23% after a follow-up period ranging from 1 to 5 years.…”
Section: Pediatric Ptsmentioning
confidence: 99%
“…164 Among a total of 977 patients with UEDVT/lower-extremity DVT, the weighted mean frequency of PTS was 26% (95% CI, [23][24][25][26][27][28]. When restricted to the 9 prospective analyses, [165][166][167][168][169][170][171][172][173] this frequency was 17% (95% CI, [14][15][16][17][18][19][20]. Only 1 prospective study has subsequently been published, in which the cumulative incidence of PTS was 23% after a follow-up period ranging from 1 to 5 years.…”
Section: Pediatric Ptsmentioning
confidence: 99%
“…A flow chart of search results and their distribution by category of publication is provided in Figure 1, showing both included [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and excluded reports. Nineteen original reports met eligibility criteria (Table 1); no systematic reviews were identified.…”
Section: Overall Search Resultsmentioning
confidence: 99%
“…In evaluating PTS, five studies 8,13,14,18,20 used a pediatric modification 8 of the Villalta scoring system for PTS in adults, 73 two studies 11,16 Reviews/commentaries (n=16) Not pediatric (n=13) Not VTE (n=8) Not followed for PTS (n=4) Single case reports (n=3) Cases selected due to PTS (n=2)…”
Section: Overall Search Resultsmentioning
confidence: 99%
“…Other pediatric reports describing the occurrence of PTS following LE-DVT reported a frequency ranging from 8.5% to 78%. It must be pointed out that these studies include either patients with VTE affecting different territories (ie, including organs), 2,[18][19][20] patients with UE and LE-DVT, 13,21 or patients with LE-DVT only. 8,22 Besides the difference in the studied populations, these reports also differ in their PTS assessment approach, and usually combine LR and Non-LR events.…”
Section: Org Frommentioning
confidence: 99%